2016
DOI: 10.3928/01477447-20160526-02
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Intravenous Tranexamic Acid in Primary Total Hip Arthroplasty

Abstract: Previous meta-analyses established that tranexamic acid confers benefits when used during total hip arthroplasty (THA). However, 2 of these meta-analyses included a variety of routes of administration of tranexamic acid in THA (topical, intravenous, oral, and intra-articular), another meta-analysis included a variety of antifibrinolytic drugs (not restricted to a single drug), and the final meta-analysis included nonrandomized controlled trials. This meta-analysis focused on a single medication, tranexamic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
4
26
1
7
Order By: Relevance
“…In this study, 96% of the patients received TXA (IV or topical), but 11% still received a transfusion despite use of strict transfusion triggers. A recent meta-analysis showed IV TXA was effective in reducing allogenic blood transfusion by 50% and limiting blood loss intraoperatively and through drains in patients undergoing primary THA [27]. Whiting et al [43] recently reported that TXA may be beneficial in patients undergoing total joint arthroplasty regardless of preoperative Hgb, with patients with anemia still seeing transfusion reductions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 96% of the patients received TXA (IV or topical), but 11% still received a transfusion despite use of strict transfusion triggers. A recent meta-analysis showed IV TXA was effective in reducing allogenic blood transfusion by 50% and limiting blood loss intraoperatively and through drains in patients undergoing primary THA [27]. Whiting et al [43] recently reported that TXA may be beneficial in patients undergoing total joint arthroplasty regardless of preoperative Hgb, with patients with anemia still seeing transfusion reductions.…”
Section: Discussionmentioning
confidence: 99%
“…As an additional concern, 24% to 44% of patients presenting for THA are anemic [39]. Although the routine use of tranexamic acid (TXA) has markedly reduced the risk of transfusion after THA, nationally, 10% of patients undergoing THA are still receiving transfusions [2,27]. Furthermore, there is a growing body of evidence to suggest that preoperative anemia and blood transfusion are associated with periprosthetic joint infection, longer length of stay (LOS), and increased risk of complications, and, in some analyses, an increased risk of death in this patient population [5-7, 13, 19, 28].…”
Section: Introductionmentioning
confidence: 99%
“…In THA and TKA, the most notable complication reported in the literature is venous thromboembolism. The vast majority of orthopaedic TXA studies show no increase in the rate of venous thromboembolism events [29][30][31]43,44]. Nishihara, et al is the only study in the recently published literature known to the authors that demonstrated a significant increase in venous thromboembolic events after TXA administration in total joint arthroplasty [18].…”
Section: Oral Usementioning
confidence: 99%
“…The most common metrics include total blood loss, intra-operative blood loss, post operative blood loss, drain output, hemoglobin reduction, and transfusion rates. Meta analyses comparing studies that use the same metrics for efficacy have widely determined TXA use is superior to placebo controls, however such analyses are rarely, if ever, able to compare studies using the exact same dosing regimens and so their conclusions are typically broadly applicable to the use of TXA but do not delve into the optimal IV and or topical dosing strategies other than speculation [6,7,[29][30][31].…”
Section: And Topical Usementioning
confidence: 99%
“…Regarding the tranexamic acid administration method, its combined (intravenous and topical) administration has been shown to be effective by Yuan et al in a meta-analysis carried out in 2016 on patients who underwent total knee replacement surgery [19]. The superiority of combined tranexamic acid administration in cases of total joint replacement surgery was also demonstrated by Xie et al in a study published in 2016 [20] and supported by Wu et al [21] in a study on the use of tranexamic acid in prosthesis revision.…”
Section: Experimental Part Materials and Methodsmentioning
confidence: 90%